PEMAKNAAN AGAMA DALAM PERSPEKTIF ANTROPOLOGI-SOSIOLOGI - A.B. Tokko (Balai Penelitian dan Pengembangan Agama Makassar, 2009)
There are many experts of various disciplines provide definition andunderstanding of religion. Some of them have been revealed in thiswriting related to anthropology and sociology only. E.B. Taylor was thefirst who studied and provided minimal definition of religion as a beliefto spiritual beings. He said that the origin of religion began when theman was aware of the existence of soul. Frazer believes that the origin ofreligion began when the man was not able to solve various problems oftheir lives due to limitation of their reasoning. Whereas Durkheim assumesthat religion was a sosial product as a collective thing with theaim to unite the members of society in a moral community. Durkheimemphasizes that nothing is wrong in religion. In reality all religions areright in its own model. This means religion is right based on the religionitself and its adherents. The writer states that the frames to understandreligious phenomena are : first, it has supernatural concept; second, ithas doctrine and teaching in the holy book, revelation, oral and writtensources; third, cosmology that is how this nature is composed followingthe perception of its followers; fourth, ritual or charity ceremony, andfifth, mediator of religion and religious group.